2004
DOI: 10.15666/aeer/03053058
|View full text |Cite
|
Sign up to set email alerts
|

STRUCTURE OF DANUBE SHAD (Alosa pontica Eichwald, 1838) SPAWNER FLOCKS MIGRATING FOR REPRODUCTION IN DANUBE RIVER (MIGRATION OF FISHES IN ROMANIAN DANUBE RIVER N o 2)

Abstract: A Ab bs st tr ra ac ct t. . The main purpose of this paper is to actualize last data on Danube shad (Alosa pontica Eichwald, 1838) migration process in Danube River. This species was widely studied last time in Danube River, but there are still some biological and ecological aspects to be revealed. Study of periodical changes in the total amount of capture and spawners structure could bring more and relevant information on presumed cyclic decrease and increase of stocks and also about the main causes of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…The authors reported that the 6-, 5-, and 3-year-old cohorts represent 19.85%, 15.62%, and 13.14%, respectively, while individuals of 7 and 2 years represent a small part of the migratory population (8.32% and 1.17%, respectively). Other authors [38] report six age groups (from 2-to 7-year-old individuals) for Pontic shad in the Danube River, Romania. In a similar study, Leonov et al (2023) [6] reported different structures of migratory Pontic shad (for the year 2022) at the Danube mouth (Sulina Branch Mm 34-18): the highest percentage of individuals captured were 3 years old (33.33%), followed by 4 years old (26.38%), while only a small percentage (11.11%) were 5 years old and 6 years old (6.94%).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that the 6-, 5-, and 3-year-old cohorts represent 19.85%, 15.62%, and 13.14%, respectively, while individuals of 7 and 2 years represent a small part of the migratory population (8.32% and 1.17%, respectively). Other authors [38] report six age groups (from 2-to 7-year-old individuals) for Pontic shad in the Danube River, Romania. In a similar study, Leonov et al (2023) [6] reported different structures of migratory Pontic shad (for the year 2022) at the Danube mouth (Sulina Branch Mm 34-18): the highest percentage of individuals captured were 3 years old (33.33%), followed by 4 years old (26.38%), while only a small percentage (11.11%) were 5 years old and 6 years old (6.94%).…”
Section: Discussionmentioning
confidence: 99%
“…Pontic shad (Alosa pontica Eichwald, 1838) is an economically important fish species which is highly appreciated by a certain number of consumers in the Lower Danube Region because it is the Christian custom of local people to eat Pontic shad during Lent (Ciolac and Patriche, 2004). Pontic shad stocks in the Black Sea and Danube River have decreased mainly due to overfishing and pollution (Navodaru, 1996;Navodaru and Waldman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Crnomorska haringa je komercijalno značajna riblja vrsta u delti Dunava. U zemljama donjeg podunavlja (Rumunija, Ukrajina i Bugarska) visoko je cenjena od strane određenog broja stanovnika koji tokom hrišćanskih praznika ovu vrstu obilato konzumiraju, naročito za vreme Velikog posta (Ciolac & Patriche, 2004).…”
Section: Slikaunclassified
“…174,0 30,6 6 (5) 4 1 27 37 380 5,227 8,750 0,284 4,545 0,170 0,398 50,2 730,9 2,557 51,2 0,0 28 37,5 452 5,968 6,694 0,242 3,629 0,161 0,323 26,0 295,6 0,726 35,0 0,0 29 37,5 395 4,545 11,091 0,318 6,818 0,273 0,273 57,5 873,7 2,409 60, (Kolarov 1985;Navodaru 1998;Navodaru et al 2001;Navodaru & Waldman, 2003;Ciolac, 2004;Ciolac & Patriche, 2004). Cren, 1951;Brown, 1957;Tesch, 1971).…”
Section: Redni Broj Uzorkaunclassified